ANALYSIS OF RESEARCH ON THE PROBLEM OF SYNTACTIC THEORIES - Isakov Shahnoza (Western European Studies, 2024)
This article is devoted to the history of the study of syntax issues and mainly reflects the periods of formation and development of the syntax of the modern Uzbek language. Mainly, this article discussed issues related to syntax from the period of the ancient Turkic language until the 20th century
Keywords: syntax; diathesis; syntactic semantics